Properties of Dispersion of Multiwalled Carbon Nanotubes as Cutting Fluid. Issue 4 (3rd July 2016) - Andhare, Atul B.; Raju, Roja Abraham
ABSTRACT: This article presents the results of experiments performed to evaluate properties of dispersion of multiwalled carbon nanotubes (MWCNT) in water with sodium dodecyl sulfate (SDS) as a dispersant. Different samples of varying concentrations of MWCNTs were prepared for the analysis and properties including thermal conductivity, pH value, viscosity, wettability, etc., were evaluated. These properties were compared with the properties of conventional cutting fluid, which was taken as a mix of water and mineral oil. It was found that the thermal conductivity of the MWCNT dispersion was higher than the conventional cutting fluid by about 42%. There was a decrease in contact angle by about 70%. Thus, dispersing MWCNTs in water with SDS increases the thermal conductivity and wettability of fluid. The pH value of fluid with 0.2 vol% MWCNTs was found to be 8.4. It thus reduced the corrosive nature of water. Nanoparticles of MWCNTs did not have much influence on the viscosity of the base fluid. Thus, the use of MWCNTs in water with SDS appeared to result in a better cutting fluid for machining than conventional cutting fluid.